First person - Eleftheria Pervolaraki (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Eleftheria Pervolaraki is first author on 'Insoluble Aβ overexpression in an App knock-in mouse model alters microstructure and gamma oscillations in the prefrontal cortex, affecting anxiety-related behaviours', published in DMM. Eleftheria conducted the research described in this article while a Research Fellow at the School of Biomedical Sciences, University of Leeds, UK. She is now Medical Science Lead for the UK at Cardinal Health, High Wycombe, Buckinghamshire, UK, working on medical devices for the management of cardiac rhythm whilst preventing infections in surgical sites.